Integrating Transcriptome-Wide Association Study and mRNA Expression Profiling Identifies Novel Genes Associated With Osteonecrosis of the Femoral Head - Ma, Mei; Li, Peilin; Liu, Li; Cheng, Shiqiang; Cheng, Bolun; Liang, Chu Jun; Tan, Sijia; Li, Wenyu; Wen, Yan; Guo, Xiong; Wu, Cuiyan (Frontiers in Genetics, 2021)
Objective: To identify novel candidate genes associated with osteonecrosis (ON). Methods: A transcriptome-wide association study (TWAS) was performed by integrating the UK Biobank genome-wide association study (GWAS) dataset of ON with pre-computed mRNA expression reference weights of muscle skeleton and blood. The ON associated genes identified by TWAS were further subjected to gene ontology (GO) enrichment analysis implemented by the DAVID tool. Finally, a trans-omics comparative analysis of TWAS and genome-wide mRNA expression profiling was conducted to detect the common genes and GO terms shared by both DNA-level TWAS and mRNA-level expression profile for ON. Results: TWAS totally identified 564 genes with PTWAS value < 0.05 for MS and blood, such as CBX1 (PTWAS=0.0001 for MS), SRPK2 (PTWAS=0.0002 for blood) and MYO5A (PTWAS=0.0005 for blood). After comparing the genes detected by TWAS with the differentially expressed genes identified by mRNA expression profiling, we detected 59 overlapped genes, such as STEAP4 (PTWAS=0.0270, FC(fold change)mRNA=7.03), RABEP1 (PTWAS=0.010, FCmRNA=2.22), and MORC3 (PTWAS=0.0053, FCmRNA=2.92). GO analysis of TWAS identified genes detected 53 GO terms for ON. Further comparing the GO analysis results of TWAS and mRNA expression profiling identified 4 overlapped GO terms, such as cysteine-type endopeptidase activity (PTWAS=0.0006, PmRNA=0.0227) and extracellular space (PTWAS=0.0342, PmRNA= 0.0012). Conclusion: Integrating TWAS and mRNA expression profiling identified multiple ON associated genes and GO terms. It provides novel clues for revealing the pathogenesis of ON.